What is fuelling privatization in health care in Nepal? - Mishra, Shiva Raj; Acharya, Pawan (Health for All, 2013)
Health service delivery is now being controlled by private hospitals and pharmaceutical companies. Health care is being sold at private sectors. Out of pocket expenditure of household is increasing sharply. Nevertheless, the government’s spending on health is stagnant. The paper discusses on three reasons; stagnant governmental spending in health, lack of governmental control in private sectors and liberal policies as the reason for increasing privatization in health care in Nepal. The very cause for the increased private control of health service delivery is the liberal attitude of government to private sector. National Health Policy, 1991 opened the door for private sector to play in health. It occurred in the name of greater involvement of private sectors. Right to health is threatened now. Revitalizing primary health care and redefining PPP is necessary in this condition. Exercise of higher degree of government control in private sectors coupled with greater investment in health by government is a necessity now. It may be hard for government to control private sectors with stronger rules and regulations. But if it is not done today it ought to be done the other day. Health for All Vol.1(1) 2013: 7-11